THE INFLUENCE OF THE RUNNER ORDERING OF THE PLANTS ON THEIR QUALITY, ROOTING AND YIELD OF STRAWBERRIES - Ana T. Selamovska, Olga V. Najdenovska (Zbornik Matice srpske za prirodne nauke /Proc. Nat. Sci, Matica Srpska Novi Sad, 2010)
In this work, we presented the influence of the runner ordering of the plants on their quality, percentage of root hair formation, and yield of two varieties of strawberries: Senga Sengana and Pocahontas depending on the time of planting. The runner ordering of plants and time of their planting have influence on the quality of plants, the percentage of root hair formation after the planting, and the yield. There has been established strong correlation among the diameter of the crown and the rooting when planted and the yield. Primary plants have higher quality, with bigger diameter of the crown, they take root better, and they have higher yield than secondary plants. Rosettes planted in August have higher yield than the ones planted later.
Keywords: primary, secondary, plants, quality, root formation, yield